“The Political Economy of Structural Change: Conceptualizing a "Just transition" in the Rhenish Lignite Mining Area - Kolde, Lisa; Wagner, Oliver (Momentum Quarterly, 2021)
Our paper develops measures for a "Just transition" governance as the basis for a political economy in structural change. For a case study in the Rhenish lignite mining area, six expert interviews were conducted with citizens' initiatives, trade unions and representatives of the state of North Rhine-Westphalia. The results show the need for political measures in various areas: While a variety of subsidy policies are being developed for the employees of established companies in the lignite industry, employees of subcontractors receive hardly any support in structural change. The latter are therefore exposed to a high risk of losing their jobs due to the phasing out of coal production. The interviews also showed that land in the Rhenish lignite mining area could become a scarce resource due to the current mining law. The actor-centered institutionalism is used to derive policy measures that meet the needs of the various interest groups. Finally, references are made to both transition management and political economy.
Keywords: Structural Change; Coal phase out; Just Transition; Political Economy; Transition Management